BOSQUES DE ALTO VALOR DE CONSERVACIÃ“N EN EL ESTADO DE HIDALGO, MÉXICO, CASO: EJIDO LA ESTANCIA, DESDE EL ASPECTO SOCIAL Y AMBIENTAL - Zavala, Erika Marlene Ortega (European Scientific Journal, ESJ, 2013)
In Mexico, the concept of forests of high conservation value has added importance because most of their land certificates have attributes of high environmental value; however, the international certification only limited to certain states of the country, for example, Durango and Oaxaca. In the state of Hidalgo, the concept is limited; none of its forests has an international certificate. Therefore, the aim of this work is to evaluate whether are attributes of high conservation value forest in La Estancia, Singuilucan, Hidalgo and determine if it is a forest of high conservation value, according to the Principles and Criteria Forest Stewardship Council (FSC), based on the Good Practice Guide FSC. After an exhaustive with government agencies, educational institutions and the owners of the place, the ejido La Estancia is credited attribute high conservation value with HCV code 5, which refers to â€œAmazing Forest Areas to Meet Basic Needs of Local Communitiesâ€, considering a Forest of High Conservation Value. It is noteworthy that La Estancia is one of the first suburbs in the state of Hidalgo who undergoes an evaluation of this type punctuating the beginning of environmental awareness.